FORMATION OF THE READINESS OF FUTURETEACHERS OF PHYSICAL CULTURE FORPROFESSIONAL ACTIVITY - Курнишев, Юрій; Палагнюк, Тарас; Гауряк, Олена; Осадець, Микола (Науковий вісник Інституту професійно-технічної освіти НАПН України. Професійна педагогіка, 2019)
У теоретичному дослідженні розкрито професійну підготовку як динамічний процес, в якому реалізуються цілі освіти й формування компетенцій. застосування отриманого соціального досвіду. У цьому аспекті освіта передбачає створення цілісної системи безперервного навчання, розвитку п виховання людини, що забезпечує підготовку в різних сферах навчальної діяльності відповідно до освітніх потреб суб'єктів педагогічного процесу. У структурі готовності майбутнього вчителя фізичної культури до професійної діяльності виділяємо мотиваційній. теоретичний та практично-творчий компоненти, кожен з яких має специфічні цільові функції. Цей склад компонентів професійної готовності забезпечує її змістову базу, що визначає можливість здійснення різних видів професійно-педагогічної діяльності в повному обсязі. Проблема обґрунтування істотних характеристик готовності вчителя фізичної культури до професійної діяльності в теорії спеціальної педагогічної освіти не нова, проте відсутнє єдине її тлумачення, а в багатьох випадках - у її ототожненні з іншими категоріями, що виражає сукупність професійно-зумовлених вимог до праці й особистості вчителя, а саме: підготовленість, компетентність, кваліфікація, майстерність, умілість, професіоналізм. Практичне значення одержаних результатів дослідження визначається тим. що його теоретичні положення і висновки створюють реальні передумови для наукового забезпечення підготовки майбутнього вчителя фізичної культури до реалізації цілісного педагогічного процесу виховання фізичної культури особистості учнів.
ФОРМУВАННЯ ГОТОВНОСТІ МАЙБУТНІХ УЧИТЕЛІВ ФІЗИЧНОЇ КУЛЬТУРИ ДО ПРОФЕСІЙНОЇ ДІЯЛЬНОСТІ
The theoretical study reveals professional training as a dynamic process in which the goals ofeducation and the formation of competencies, application of the received social experience are realized. In thisaspect, education involves the creation of a holistic system of lifelong learning, development and upbringing of aperson that provides training in various spheres of educational activity in accordance with the educational needsof the subjects of the pedagogical process.The training of the specialist, in particular a teacher, has its own peculiarities depending on the chosen specialty.Therefore, it is appropriate to consider the peculiarities of the preparation of the future teacher of physical cultureat the pedagogical institution of higher education.The contents of the preparation of the teacher of physical culture for professional activity in a comprehensiveeducational institution, that is, the implementation of the holistic pedagogical process of upbringing the physicalculture of the person, is based on the expanded interpretation of the content of pedagogical education.In the structure of readiness for the professional activity of the future teacher of physical education, wedistinguish the motivational, theoretical and practical-creative components, each of which has specific targetfunctions and in this sense relatively independent. This structure of the components of professional preparednessprovides its containing basis, which determines the possibility of implementing various types of vocational andpedagogical activities in full.The problem of substantiating the essential characteristics of the readiness of the teacher of physical culturefor professional activity in the theory of special pedagogical education is not new, but there is no a singleinterpretation of it, and in many cases – it is identified with other categories. This identification expresses thetotality of professionally determined requirements to work and the teacher's personality, namely: preparedness,competence, qualification, mastery, artfulness, professionalism.The practical significance of the received results of the study is determined by the fact that its theoreticalpositions and conclusions create real prerequisites for the scientific provision of the training of the futureteacher of physical culture and the implementation of a holistic pedagogical process of promoting the physicalculture of the students' personality.
Keywords: readiness for professional activity, components, future teacher of physical culture, personality